Analisis the Strategy Method Guru Pendidikan Agama Islam dalam Upaya Mengajarkan Movement Againts Radicalism Values kepada Peserta Didik MTs. (Plus) Bahrul Ulum Tambakberas - Wahyudi Wahyudi; Muh Khofif Luthfi Rohman (Risda: Jurnal Pemikiran dan Pendidikan Islam, 2022)
This research departs from the phenomenon of radicalism that occurs in society, especially in the world of education. This research is a qualitative research with descriptive-qualitative research method. The results of this study indicate that first, Analysis teacher's strategy in an effort to teach Movement Againts radicalism values, That is teachers 1) Instilling the concept of Akidah Akhlaq/monotheism, 2) Teaching about Aswajan Amaliyah An-Nahdliyah, 3) Holding Firm to the Qur'an and Hadith, 4) Choosing Friends in Association. Second, the most effective methods in an effort to teach Movement Againts radicalism values ​​are: 1) Through a program of habituation of religious 2) Through programs Commemoration of Islamic holidays 3) Through programs to commemorate National Holidays Then the third, are the supporting and inhibiting factors, That is 1) the misuse of information technology (IT) which is often misused by students, 2) the lack of parental support for school policies. 3) lack of cooperationbetweenteachers and students regarding the understanding of radicalism.4) lack of parental participation in providing an understanding of the dangers of radicalism when they are at home. 5) Discipline of students who are less stable from the lack of cooperation between the pesantren administrator and the school administrator